2005
DOI: 10.1099/vir.0.80449-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human immunodeficiency virus 1 transcription by nef microRNA

Abstract: MicroRNAs (miRNAs) are~21-25 nt long and interact with mRNAs to lead to either translational repression or RNA cleavage through RNA interference. A previous study showed that human immunodeficiency virus 1 (HIV-1) nef dsRNA from AIDS patients who are long-term non-progressors inhibited HIV-1 transcription. In the study reported here, nef-derived miRNAs in HIV-1-infected and nef transduced cells were identified, and showed that HIV-1 transcription was suppressed by nef-expressing miRNA, miR-N367, in human T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(124 citation statements)
references
References 40 publications
3
117
1
3
Order By: Relevance
“…Several recent reports describe miRNAs cloned from a variety of viruses such as herpes viruses 38,39 and human immunodeficiency virus 1 (HIV-1). 40 Pfeffer et al 24 identified five miRNAs in Epstein-Barr virus (EBV) through cloning of RNA from latently infected Burkitt's lymphoma cells. The same group 39 also found nine miRNAs encoded by human cytomegalovirus (HCMV) and, simultaneously, with Cai et al 38 found 11 miRNAs from Kaposi's sarcomaassociated virus (KSHV).…”
Section: Viral Mirnas and Human Mirnas Targeted Against Viral Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent reports describe miRNAs cloned from a variety of viruses such as herpes viruses 38,39 and human immunodeficiency virus 1 (HIV-1). 40 Pfeffer et al 24 identified five miRNAs in Epstein-Barr virus (EBV) through cloning of RNA from latently infected Burkitt's lymphoma cells. The same group 39 also found nine miRNAs encoded by human cytomegalovirus (HCMV) and, simultaneously, with Cai et al 38 found 11 miRNAs from Kaposi's sarcomaassociated virus (KSHV).…”
Section: Viral Mirnas and Human Mirnas Targeted Against Viral Genesmentioning
confidence: 99%
“…39 The same authors also predicted the occurrence of miRNAs in the genome of the smaller single-stranded RNA viruses, measles virus and yellow fever virus, although in the latter case this was not confirmed by cloning. Omoto et al 40,42 identified an miRNA expressed from the HIV-1 nef-gene of AIDS patients who are long-term disease nonprogressors, and which encodes an miRNA that may suppress both Nef function and HIV-1 virulence through RNA silencing. Further putative HIV-1-derived miRNAs targeted against the T cell receptors CD4 and CD28, and several interleukins were proposed in a recent computational study.…”
Section: Viral Mirnas and Human Mirnas Targeted Against Viral Genesmentioning
confidence: 99%
“…Lecellier et al (2005) found that a cellular miRNA, miR-32, mediated antiviral defense in human cells, and regulated primate foamy virus type I (PFV-1) proliferation. Several mammalian viruses, including the herpesvirus family, such as Epstein-Barr virus (EBV), simian virus 40 (SV40), and Kaposi sarcoma-associated virus, have been found to code miRNAs (Pfeffer et al, , 2005Cai et al, 2005;Grey et al, 2005;Omoto and Fujii, 2005;Sullivan et al, 2005;Sullivan and Ganem, 2005a,b;Cai and Cullen, 2006;Jiang et al, 2006;Schuetz and Sarnow, 2006;Simon-Mateo and Garcia, 2006). Although the function of these coding miRNAs is still unknown, it may play a role in human disease development.…”
Section: Functions Of Micrornas In Animalsmentioning
confidence: 99%
“…These authors showed that the HIV-1 TAR-RNA structure (in the absence of the Tat protein) is quite similar to that of dsRNA in the way to activate PKR and therefore to block protein synthesis. Alternatively, virus-derived dsRNA structures such as TAR-RNA, RNA transcribed from the Rev response element (RRE) and/or the nef and env genes [25], or virus-encoded siRNA, can serve as substrates for the Dicer complex. These HIV-specific siRNA complexes could promote HIV-RNA degradation and induce a latency state.…”
Section: Rnai and Hiv-1 Pathogenesismentioning
confidence: 99%
“…Recent reports have also shown that viruses encode miRNA [24][25][26][27][28], and it was explored the participation of viral and cellular host regulatory RNAs in the intricate host-pathogen interaction networks reviewed in References [29][30][31][32][33]. In addition, a distinct class of longer 28 nt siRNAs, known as repeat-associated small interfering RNAs (rasiRNAs) was recently reported, and acts to silence the expression of transposon chromosomal copies and transposon-like repeats [34].…”
Section: Introductionmentioning
confidence: 99%